2008
DOI: 10.1039/b718116g
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical parameters and techniques in drug development, with an emphasis on quinones and related compounds

Abstract: This review article summarizes recent applications of electrochemical techniques to redox-active drug development and mechanistic studies. It includes a general introduction to the use of electrochemistry in biology, with a focus on how electrochemistry can uniquely provide both kinetic and thermodynamic information. A number of studies are reported from the literature and the authors' laboratories, including the investigation of reactive oxygen species, biooxidative/bioreductive activation of pro-drugs, and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
164
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(173 citation statements)
references
References 149 publications
(189 reference statements)
3
164
0
6
Order By: Relevance
“…[36][37][38][39][40][41][42] As already described, oxidative stress leading to DNA damage and alkylation of nuclear cellular nucleophiles are the two major mechanisms of quinone cytotoxicity. 9,12,16,43 Concerning the results in the present study, a typical electrochemical behavior (in aprotic medium) is observed for oncocalyxone A, represented by diffusional two quasi-reversible reduction systems, with a well-stabilized anion radical as evidenced by ESR analysis. Oncocalyxone A has shown significant DNA activity, represented by the decrease and shift of oxidation peaks of guanosine/guanine and adenosine/adenine.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…[36][37][38][39][40][41][42] As already described, oxidative stress leading to DNA damage and alkylation of nuclear cellular nucleophiles are the two major mechanisms of quinone cytotoxicity. 9,12,16,43 Concerning the results in the present study, a typical electrochemical behavior (in aprotic medium) is observed for oncocalyxone A, represented by diffusional two quasi-reversible reduction systems, with a well-stabilized anion radical as evidenced by ESR analysis. Oncocalyxone A has shown significant DNA activity, represented by the decrease and shift of oxidation peaks of guanosine/guanine and adenosine/adenine.…”
Section: Discussionsupporting
confidence: 53%
“…3,4,[5][6][7][8] Oncocalyxone A also shows differential antitumor activity against the murine tumors Ehrlich carcinoma, sarcoma 180 and L1210 leukemia. 8 In general, two major mechanisms of quinone cytotoxicity have been proposed: stimulation of oxidative stress and alkylation of cellular nucleophiles, which encompass large range of biomolecules, 9 such as DNA and some enzymes, e.g., topoisomerase and protein tyrosine phosphatases, mainly those with thiol groups. 10 Oncocalyxone A, a para-benzoquinone with an extended conjugated dienone scaffold, may possibly function as a reactive Michael acceptor toward nucleophilic sites on proteins, for example, cysteinyl thiol groups, or on DNA.…”
Section: Introductionmentioning
confidence: 99%
“…6 A recent review shows how drug development can be aided by electrochemical investigations, with a focus on quinone compounds. 7 The studies of quinone electrochemistry also contributed to our understanding of proton-coupled electron transfer (PCET) reactions. A review on electrochemical approach to PCET mechanism devotes a great portion to quinones.…”
Section: Introductionmentioning
confidence: 99%
“…This property can be related to their biological activity. [258][259][260] The potential of quinone compounds to participate in redox cycling is mainly dependent on the stability of the semiquinone radical relative to the quinone and the quinol forms. A simple and practical method for calculating thermodynamic parameters necessary to estimate semiquinone stability constants and redox potentials for quinone natural products has been reported by Cape et al 261 utilizing DFT-B3LYP method.…”
mentioning
confidence: 99%